Uji Preklinis 177Lu-DOTA-Trastuzumab: Radiofarmaseutika Potensial untuk Terapi Kanker Payudara HER-2 Positif - MARTALENA RAMLI; BASUKI HIDAYAT; SRI AGUSWARINI; KARYADI KARYADI; CAHYA NOVA ARDIYATNO; HAMMAD SUBUR; TITIS SEKAR HUMANI; RIEN RITAWIDYA; ABDUL MUTALIB; JOHAN MASJHUR (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Radiopharmaceutical 177Lu-(1,4,7,10-tetraazacyclododecane-N,N’,N”,N”’-tetra acetic acid)-trastuzumab (177Lu-DOTA-trastuzumab), based on antihuman epithelial receptor type 2 (HER-2) monoclonal antibody which is expected to be potential for diagnostic and therapeutic agent of breast cancer positive HER-2, had been successfully prepared with radiochemical purity of > 99%. Preclinical studies aimed in providing basic data for clinical trial and particularly in finding out the effectiveness of 177Lu-DOTA-trastuzumab in killing cancer cells which over express HER-2, have been performed. The data included urine and faeces clearance tests, imaging with gamma camera and cytotoxicity test. The results showed that the excretion of radioactivity post injection of 177Lu-DOTA-trastuzumab in normal rats were more rapid through urine as compared to the excretion through faeces. The gamma camera image on normal rat 144 hours post injection of 177Lu-DOTA-trastuzumab showed that there was remaining a trace of radioactivity in hepatic area. The residue of radioactivity (< 5%, quantified by biodistribution test) was found to be relatively lower than reported for 111In-NSL-trastuzumab. However, this residue of radioactivity has to be seriously considered when 177Lu-DOTA-trastuzumab is going to be applied for treatment of cancer. Cytotoxicity test showed that 177Lu-DOTA-trastuzumab was far more effective in killing cancer cells positive HER-2 (SKOV-3 cell lines) than that of trastuzumab.